MANIFESTASI AMAE DALAM ANIME JINSEI - I Nyoman Pradnya Mahajana; Made Henra Dwikarmawan Sudipa (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2026)
The research aims to analyze the manifestations amae in the anime jinsei. The data were collected from the anime consist of 13 episodes. In qualitative analyze, there are three components, namely observation, data presentation and drawing conclusions. The theories used in this research are literary psychology theory and amae theory by doi (1985). Based on the analysis, 5 data related to amae were found. Namely, about affection, dependence and giving attention. In the affection section there is data that explain that the Akamatsu does not allow the character Endou enter the room alone. In the dependency section there is a grandfather character who always cooks for the character Fumi. Meanwhile, the manifestation of attention explains the Ikumi character who helped his grandfather who was falling from the highway.